2014
DOI: 10.1097/inf.0000000000000050
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic and Genotypic Characteristics of Rotavirus Strains Detected in Children Less Than 5 Years of Age With Gastroenteritis Treated at 3 Pediatric Hospitals in Zimbabwe During 2008–2011

Abstract: Rotavirus causes a significant disease burden among children <5 years of age in Zimbabwe. This active surveillance system can serve as a platform to monitor the impact of rotavirus vaccine on disease burden following vaccine introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
5
8
1
Order By: Relevance
“…Our findings have shown that 91% of infected children are < 2 years of age with the highest prevalence (44.7%) between 6 -11 months old which is comparable with previous studies in Zimbabwe, Uganda and Nigeria [9][10][11]. This onset of infection correlates very well with the decline of maternally acquired antibodies that disappear around 5 months of age.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our findings have shown that 91% of infected children are < 2 years of age with the highest prevalence (44.7%) between 6 -11 months old which is comparable with previous studies in Zimbabwe, Uganda and Nigeria [9][10][11]. This onset of infection correlates very well with the decline of maternally acquired antibodies that disappear around 5 months of age.…”
Section: Discussionsupporting
confidence: 78%
“…In temperate climates, rotavirus diarrhoea is predominantly a winter disease and few or no cases occur other than at the seasonal peak (Ho eta al 1988, LeBaron et al 1990, Ryan et al 1996. Similar findings were reported in Zimbabwe [9] which has a similar temperate climate like Swaziland.…”
Section: Discussionsupporting
confidence: 77%
“…Over the years, this surveillance network has determined which strains are circulating in Africa using the RVA binary classification system by genotyping the two outer capsid proteins (G and P). This method has identified infections containing multiple G and/or P genotypes, as reported from different African countries (Abebe et al, 2014; Boula et al, 2014; Hokororo et al, 2014; Kiulia et al, 2014; Mukaratirwa et al, 2014; Odiit et al, 2014; Pursem et al, 2014; Seheri et al, 2014; Tsolenyanu et al, 2014). Most strains with G1P[8], G3P[8], G4P[8] and G9P[8] G and P genotype combinations usually belong to the Wa-like genogroup because they have a Wa-like genotype constellation (Gx-P[8]-I1-R1-C1-M1-A1-N1-T1-E1-H1) composed primarily of genotype 1 genes, whereas G2P[4] strains are considered DS-1-like genogroup members because they have a DS-1-like constellation (G2-P[4]-I2-R2-C2-M2-A2-N2-T2-E2-H2) composed of genotype 2 genes (Matthijnssens et al, 2008, 2011; Matthijnssens and Van Ranst, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, strain diversity is extensive, and several G and P genotype combinations have been reported from multiple countries. These include, but are not limited to, G1P[6], G1P[8], G2P[4], G2P[6], G3P[6], G8P[6], G9P[8] and G12P[8], as well as mixed/multiple G and/or P types and also stains regarded as untypeable with available primer sets (Abebe et al, 2014; Banga-Mingo et al, 2014; Boula et al, 2014; Hokororo et al, 2014; Kiulia et al, 2014; Mukaratirwa et al, 2014; Odiit et al, 2014; Page et al, 2010; Pukuta et al,2014; Pursem et al, 2014; Seheri et al, 2014; Tsolenyanu et al, 2014). In addition, some studies have also reported the detection of animal or animal-human reassortant strains circulating among humans (Esona et al, 2009, Esona et al, 2010; Jere et al, 2012; 2014; Page et al, 2010; Nyaga et al, 2013; 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Zimbabwe, diarrhea is the second leading cause of childhood deaths, contributing to 10% to 15% of deaths in children <5 years of age in 2015 [1, 4]; rotavirus accounted for 41–56% of acute diarrhea hospitalizations prior to vaccine introduction [5]. In May 2014, the Government of Zimbabwe introduced the 2-dose, oral, monovalent, live attenuated human rotavirus vaccine, Rotarix (GlaxoSmithKline), into its Expanded Programme on Immunization (EPI).…”
Section: Introductionmentioning
confidence: 99%